1977
DOI: 10.1070/qe1977v007n07abeh012668
|View full text |Cite
|
Sign up to set email alerts
|

Role of the parametric and Raman processes in the generation of the second axial Stokes component of the stimulated Raman scattering

Abstract: thirty seconds (determined by the setting of VRJ, which allows condenser C2 to charge up to its full high voltage, V2 ikes and relay RLB operates:(i) opening RLB, and releasing relay RLA;(ii) closing RLB,. 3. Closure of RLB, applies a negative pulse to the control grid of the cold cathode tetrode V,, as a result of which the anode to cathode path immediately becomes conducting, and condenser C8 discharges through the primary of the ignition coil TR4. This produces in the secondary a damped oscillatory transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…For instance it is possible to convert visible radiation into IR light using the 2nd Stokes emission. In literature many papers have shown that the Raman generation of the 2nd Stokes wave is stimulated by mixing processes [1][2][3][4][5][6][7][8][9]. The mixing effect on the onset of the 2nd Stokes generation has been theoretically calculated and experimentally observed in [9], in conditions where no annular wave formation was detected because of high pressure and weak focusing.…”
Section: Introduction and Theorymentioning
confidence: 96%
See 3 more Smart Citations
“…For instance it is possible to convert visible radiation into IR light using the 2nd Stokes emission. In literature many papers have shown that the Raman generation of the 2nd Stokes wave is stimulated by mixing processes [1][2][3][4][5][6][7][8][9]. The mixing effect on the onset of the 2nd Stokes generation has been theoretically calculated and experimentally observed in [9], in conditions where no annular wave formation was detected because of high pressure and weak focusing.…”
Section: Introduction and Theorymentioning
confidence: 96%
“…In literature many papers have shown that the Raman generation of the 2nd Stokes wave is stimulated by mixing processes [1][2][3][4][5][6][7][8][9]. The mixing effect on the onset of the 2nd Stokes generation has been theoretically calculated and experimentally observed in [9], in conditions where no annular wave formation was detected because of high pressure and weak focusing. In that case the mixing effect induces an ''off-phase" seed radiation at the 2nd Stokes frequency much larger than the background one, that produces a lowering of the 2nd Stokes threshold, as observed in [5,6,9].…”
Section: Introduction and Theorymentioning
confidence: 96%
See 2 more Smart Citations
“…Under intense pumping conditions the stimulated Raman scattering depletes the pump laser and the generated Stokes light becomes the pump source of higher order Stokes light generation by the processes v sn~* v s«+i+ v v [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Four photon mixing processes like v s l + v sl -+ v L + v S2 may contribute to the higher order Stokes light generation if the corresponding phasematching angles are small [15][16][17]. Parametric Stokes anti-Stokes coupling [1][2][3][4][5], v L +v L ->v sl + v AS1 , and higher order anti-Stokes coupling, like v AS/l + v L ->v sl…”
Section: Pacs: 4265 Cmentioning
confidence: 99%